2013
DOI: 10.1115/1.4025448
|View full text |Cite
|
Sign up to set email alerts
|

A Head and Neck Support Device for Inducing Local Hypothermia

Abstract: The present work describes the design of a device/system intended to induce local mild hypothermia by simultaneously cooling a patient's head and neck. The therapeutic goal is to lower the head and neck temperatures to 33-35 C, while leaving the core body temperature unchanged. The device works by circulating a cold fluid around the exterior of the head and neck. The head surface area is separated into five different cooling zones. Each zone has a cooling coil and can be independently controlled. The cooling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Selective brain hypothermia is an attractive alternative to systemic hypothermia, providing focused cooling of the injured organ and avoiding the complications of systemic hypothermia, including intubation, shivering, pneumonia, altered coagulability, and cold-induced stress reactions (58). A variety of devices and strategies have been developed to induce selective brain hypothermia and tested in preclinical models and early human clinical trials, including intranasal selective hypothermia, transvenous endovascular cooling, extraluminal vascular cooling, and epidural cerebral cooling (63)(64)(65)(66)(67)(68)(69)(70)(71)(72). However, advance of these devices in clinical development has been constrained by slow onset of cooling induced by external cerebral cooling techniques and procedural time delay needed to place internal nasopharyngeal cooling devices.…”
Section: The Promises Of Adjunct Endovascular Brain Hypothermiamentioning
confidence: 99%
“…Selective brain hypothermia is an attractive alternative to systemic hypothermia, providing focused cooling of the injured organ and avoiding the complications of systemic hypothermia, including intubation, shivering, pneumonia, altered coagulability, and cold-induced stress reactions (58). A variety of devices and strategies have been developed to induce selective brain hypothermia and tested in preclinical models and early human clinical trials, including intranasal selective hypothermia, transvenous endovascular cooling, extraluminal vascular cooling, and epidural cerebral cooling (63)(64)(65)(66)(67)(68)(69)(70)(71)(72). However, advance of these devices in clinical development has been constrained by slow onset of cooling induced by external cerebral cooling techniques and procedural time delay needed to place internal nasopharyngeal cooling devices.…”
Section: The Promises Of Adjunct Endovascular Brain Hypothermiamentioning
confidence: 99%
“…This feasibility trial of five patients demonstrated that use of the NeuroSave system to irrigate the pharynx and upper esophagus with chilled saline was well tolerated and cooled the brain faster than any currently marketed device other than a CPB circuit. [32][33][34][35] Several adverse events, common in the studied population, were observed and none were deemed to be related to the NeuroSave system (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although, for the whole body, even small deviations from physiological temperature (36.6 °C) can cause irreversible changes or death, local temperature changes are well-tolerated Local temperature control has been successfully employed in medical treatments. For example, locally induced hypothermia is routinely used to decrease swelling and to lower clotting threshold in the treatment of physical body trauma. …”
mentioning
confidence: 99%